2021
DOI: 10.1002/aepp.13212
|View full text |Cite
|
Sign up to set email alerts
|

Contract farming and the adoption of sustainable farm practices: Empirical evidence from cashew farmers in Ghana

Abstract: Contract farming has been shown to increase agricultural productivity and thus welfare of farmers in developing countries. However, studies that look at the potential environmental effects of contract farming remain quite scanty. This is however crucial, since contract farming may contribute to intensification in cultivation of the contracted crops, in terms of area and the intensity of inputs used. This study investigates the impact of participation in contract farming on sustainable farm practices, using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The study's outcome is in conformity with the results of Workineh et al (2020) who found distance as a decreasing function of probability of adoption of farm innovations such as wheat varieties. Many pieces of literature (e.g., Dubbert et al, 2021, Danso-Abbeam et al, 2022a…”
Section: Definitions Of Variables and Summary Statisticsmentioning
confidence: 99%
“…The study's outcome is in conformity with the results of Workineh et al (2020) who found distance as a decreasing function of probability of adoption of farm innovations such as wheat varieties. Many pieces of literature (e.g., Dubbert et al, 2021, Danso-Abbeam et al, 2022a…”
Section: Definitions Of Variables and Summary Statisticsmentioning
confidence: 99%
“…Cashew nuts for the past decade have become popular on the international market, increasing export (Dubbert et al, 2021). In 2019, Ghana on the international market contributed about 171,924 mt of nuts to the world production volume, thus signifying the importance attached to cashew production in this part of the world (Akyereko et al, 2022).…”
mentioning
confidence: 99%
“…Most of the literature on food chains that has studied adoption of SAPs focuses on the dyadic relationship between farmers and lead firms (Freidberg, 2020), specifically on the role of lead firms and the governance forms used to coordinate the adoption of SAPs with farmers (Achabou et al, 2017;Freidberg, 2020). To pursue the adoption of SAPs, lead firms usually operate through hybrid governance forms (e.g., formal contracts) and, in parallel, stimulate close relationships with farmers to sustain the relationship and create mutual benefits (Dubbert et al, 2021;Touboulic et al, 2021;Veldwisch and Woodhouse, 2021). Hence, this literature has investigated how contractual provisions (e.g., quality, price, payment schemes) and relationship attributes (e.g., trust and satisfaction) between farmers and lead firms can support farmers to adopt SAPs (Gualandris and Kalchschmidt 2016).…”
Section: Farmer-buyer Relationshipsmentioning
confidence: 99%
“…However, coordination works better if farmers and buyers maintain close and sustainable business relationships based on long-lasting, stable and mutual advantages. Studies have found that lead firms involve farmers through formal contracts (Bush et al, 2015;Ghadimi et al, 2016;Freidberg, 2020), in which contractual provisions specify SAP adoption (e.g., the intensity and types of inputs used) (Ghadimi et al, 2016;Thomson et al, 2020;Dubbert et al, 2021). However, Touboulic et al, (2021) stress that the pressure to adopt SAPs is effective only when there is a close, mutually trustworthy, relationship between the lead firm and the farmer.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation